2021
DOI: 10.1093/jisesa/ieab094
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of Differentially Expressed Genes in Myzus persicae (Hemiptera: Aphididae) in Response to Trans-anethole

Abstract: Plant essential oils, with high bioactivity and biodegradability, provide promising alternatives to synthetic pesticides for pest control. Trans-anethole is the major component of essential oil from star anise, Illicium verum Hook. The compound has a strong contact toxicity against the green peach aphid, Myzus persicae (Sulzer) (Hemiptera: Aphididae), which is a major insect pest of many vegetables and crops. However, little information is known about how M. persicae responds to trans-anethole at the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…9−11 Also, the nAChRs play a central role in fast excitatory synaptic transmission in the insect central nervous system 12 and have been an important neuronal target for the control of vector insects. 13,14 As a highly efficient pharmacophore, anethole has a broad range of biological activities against vector insects, including mosquitoes, 15−19 Rhipicephalus microplus, Rhipicephalus annulatus, and Dermacentor nitens, 20,21 Myzus persicae, 22,23 Musca domestica, 24 Bemisia tabaci, 25 and Periplaneta americana, 26 with neurotoxic actions of acetylcholinesterase, GABA receptors, and octopamine receptors. 27−29 lead candidate for the development of insect vector control agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9−11 Also, the nAChRs play a central role in fast excitatory synaptic transmission in the insect central nervous system 12 and have been an important neuronal target for the control of vector insects. 13,14 As a highly efficient pharmacophore, anethole has a broad range of biological activities against vector insects, including mosquitoes, 15−19 Rhipicephalus microplus, Rhipicephalus annulatus, and Dermacentor nitens, 20,21 Myzus persicae, 22,23 Musca domestica, 24 Bemisia tabaci, 25 and Periplaneta americana, 26 with neurotoxic actions of acetylcholinesterase, GABA receptors, and octopamine receptors. 27−29 lead candidate for the development of insect vector control agents.…”
Section: Introductionmentioning
confidence: 99%
“…In order to optimize the mesoionic lead compound, 2,2,2-trifluorethyl and (2-chlorothiazol-5-yl)­methyl group replace the n -propyl group at the 1-position of the mesoionic core based on bioisosteric replacement strategy (compounds 2 and 3 ) showing excellent insecticidal activity against many kinds of pests . Further optimization based on compound 3 led to the discovery of triflumezopyrim ( 4 ) and dicloromezotiaz ( 5 ) as a hemiptera and lepidoptera insecticide by the bioisosteric replacement strategy (Figure ), , which exert their insecticidal action by inhibiting nicotinic acetylcholine receptors (nAChRs). Also, the nAChRs play a central role in fast excitatory synaptic transmission in the insect central nervous system and have been an important neuronal target for the control of vector insects. , As a highly efficient pharmacophore, anethole has a broad range of biological activities against vector insects, including mosquitoes, Rhipicephalus microplus, Rhipicephalus annulatus, and Dermacentor nitens, , Myzus persicae, , Musca domestica, Bemisia tabaci, and Periplaneta americana, with neurotoxic actions of acetylcholinesterase, GABA receptors, and octopamine receptors. It is a potential chemical probe and a lead candidate for the development of insect vector control agents …”
Section: Introductionmentioning
confidence: 99%
“…One mechanism of plant essential oils is thought to be inhibition of the oxidative system of insects, which causes generation of reactive oxygen species and induces oxidative stress ( Chen et al, 2021a ). Recent transcriptome research has demonstrated that insects upregulate the expression of their detoxifying enzyme genes in response to plant secondary compounds, maintaining their ability to function normally ( Sierra et al, 2021 ; Ding et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%